Influence of Organizational Culture and Competence on Business Model of Industrial Revolution 4.0. As Well As Its Implications on The Company's Performance - Erwin Yulianto; Firman Ismanto (Indonesian Journal of Social Research (IJSR), 2020)
: This research aims to find out and analyze the influence of organizational culture and competence on the business model of industrial revolution 4.0. and its implications on the performance of companies located in bank bjb. Currently, the performance of the bank's Business Work Unit, especially from profit growth indicators, quality of services and quality assets is still volatile and tends to decline. The research method used is descriptive and verifikative analysis. Data collection techniques used are using questionnaires in the field accompanied by literature studies, sampling techniques used, namely Proportionate Stratified Random Sampling. Data analysis techniques using Path Analysis. The results of descriptive analysis showed that in general the culture of the organization and competence fall into a high category, judging by the business model of the Industrial Revolution 4.0. and the company's performance in general is still in the category of sufficient. The results of verifikatif analysis showed that there is an influence of organizational culture and competence on the business model of Industrial Revolution 4.0. both partially and simultaneously in improving the company's performance. In part, competence was more dominant in influencing the implementation of the business model of the Industrial Revolution 4.0. The results of the research are expected to be a useful contribution and input for the Bank BJB's Business Work Unit in improving the company's performance, through an in-depth review of organizational culture, competencies, and business models of the Industrial Revolution 4.0.